Seleção, avaliação e utilização de uma levedura personalizada para a produção de etanol - Vicente, Fernando Antônio da Costa Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Ethanol production in Brazil is based on fed-batch fermentations in large volume tanks (250,000 to 3,000,000 liters), with fast fermentations (6-12hours) and high concentrations of yeast (8-15% w/v). However, this process is subject to contamination by wild Saccharomyces strains that may cause serious problems such as low fermentation yield, flocculation and residual sugars in the wine. The research objective was to select a Saccharomyces strain, more adapted to fermentation process of Alta Mogiana mill that might be a robust yeast, dominant and persistent in the industrial fermentation process during the harvesting season. Experiments in industrial scale were conducted at Alta Mogiana mill, located in São Joaquim da Barra region, state of São Paulo, Brazil. The main steps were: 1) monitoring the population of dominant and persistent strains by karyotyping; 2) evaluation of the fermentation performance of strains in laboratory-scale; 3) re-introducing of the selected strain in the industrial fermentation process; and, 4) evaluation of the strain performance in industrial scale. The results enabled the selection of a strain (yeast UAM) that dominated the microbiota of fermentation tanks and remained in the fermentation process during all harvesting season. This strain enabled industrial gains such as the increase of alcoholic content in wine from 8 to 10%, reduction of vinasse volumes from 11.44 to 10.23 L/L ethanol and lowering the contamination by wild Saccharomyces. Moreover, this strain provided savings of thermal energy and bagasse (15,000 ton/ harvest) and contributed to increase the industrial efficiency of sugar recovery (from 88 to 92 % of processed sugar). These results demonstrate the feasibility and benefits for Brazilian distilleries to have their own yeast strain selected among the indigenous ...

A produção de etanol no Brasil é baseada, principalmente, em processo de fermentação por batelada alimentada, em tanques de grande volume (250.000 a 3.000.000 de litros), com fermentação rápida (6-12 horas), utilizando altas concentrações de levedura (8-15% p/v). Entretanto, este processo está sujeito a contaminação por cepas Saccharomyces do meio ambiente designadas selvagens as quais podem causar sérios problemas ao processo fermentativo como fermentação lenta, floculação do fermento e aumento do açúcar residual no mosto fermentado. O objetivo do trabalho foi selecionar uma linhagem de Saccharomyces cerevisiae mais adaptada ao processo fermentativo da Usina Alta Mogiana e que constituísse um fermento robusto, dominante e persistente na fermentação industrial ao longo da safra. Os experimentos em escala industrial foram conduzidos na Usina Alta Mogiana, localizada na região de São Joaquim da Barra, estado de São Paulo. As principais etapas foram: 1) monitoramento da população de linhagens dominantes e persistentes nas fermentações por cariotipagem; 2) avaliação do desempenho fermentativo das linhagens em escala de laboratório; 3) reintrodução da cepa selecionada no processo fermentativo industrial, 4) avaliação do desempenho da cepa na escala industrial. Os resultados permitiram a seleção de uma linhagem (levedura UAM) que dominou a microbiota da dorna e permaneceu no processo fermentativo durante toda a safra. Esta linhagem permitiu os seguintes ganhos industriais: incremento no teor alcoólico do vinho de 8 para 10%, reduzindo o volume de vinhaça de 11,44 para 10,23 L/L etanol, diminuiu a contaminação por Saccharomyces selvagens, proporcionou uma economia de energia térmica e bagaço (15.000 ton/safra) e contribuiu para aumentar a eficiência industrial de recuperação de açúcar (de 88 para 92% do açúcar processado). Esses resultados demonstraram a viabilidade e vantagens das usinas...
Keywords: Microbiologia industrial; Levedos - Aplicações industriais; Saccharomyces cerevisiae; Cariotipagem; Fermentação; Etanol - Industria